Cross-provincial Cross-region Power Trading Optimization Modeling - Chen, Jing-wen; Xiao, Yan; Dang, Hong-she; Zhang, Rong (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: China's power resources are unevenly distributed in geography, and the supply-demand imbalance becomes worse due to regional economic disparities. It is essential to optimize the allocation of power resources through cross-provincial and cross-regional power trading. Methods: This paper uses load forecasting, transaction subject data declaration, and route optimization models to achieve optimal allocation of electricity and power resources cross-provincial and cross-regional and maximize social benefits. Gray theory is used to predict the medium and longterm loads, while multi-agent technology is used to report the power trading price. Results: Cross-provincial and cross-regional power trading become a network flow problem, through which we can find the optimized complete trading paths. Conclusion: Numerical case study results have verified the efficiency of the proposed method in optimizing power allocation across provinces and regions.
Keywords: load prediction